UPAYA MEMERANGI TINDAKAN PENCUCIAN UANG (MONEY LAUNDRING) DI INDONESIA - Waluyo, Edi (Faculty of Law, Universitas Jenderal Soedirman, 2009)
The problems of prevention of money loundry is not easy and simple problem, world power Problems of prevention of wash of money is not easy and simple problem, even for international. At this millennium, the phenomenon fight money laundry is improving which in international scale by various states, and in domestic level. The international effort is not only emphasizing to the making of law and regulation that instructed to fight crimes organized especially trafficking, drug organized but also other various crime. Indonesia effort to fight in money laundry by gradual through two policy of law, that is with prevention approach in banking law such as Knowing Your Customer Principle and policy of Criminal law as repressive approach in money laundry as arranged in Law No. 15 Year 2002 jo Law No. 25 Year 2003. Kata Kunci : money laundering, Knowing Your Customer Principle